THE REFORM OF THEOLOGICAL EDUCATION IN NIGERIA/AFRICA: Intercultural Transformation - Uka, E M (Journal of Dharma, 1999)
By the turn of the millennium, theological education in Nigeria will be slightly more than 50 years old, having been initiated in 19481 While the need to celebrate the progress and achievements of this sort of education must be recognized, there seems to me to be a parallel necessity to review its ideological foundation in the Nigerian and by extension, African context. This is with a view to fortify such foundations at points of apparent weakness, and to propose means of improving its seeming lack of a Nigerian-cum-African orientation from the outset, especially in the area of curriculam and methodology of teaching.